EFFECT OF POLYETHYLENE GLYCOL AND SALICYLIC ACID ON SOME VEGETATIVE GROWTH TRAITS OF DATE PALM TISSUE CULTURE DERIVED PLANTS - & et al, Khierallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted in the greenhouse of Al-Rabee Research Station of the Department of Horticulture, Ministry of Agriculture for the 2011-2012 season in order to examine the effect of foliar application of various combinations of polyethylene glycol and salicylic acid levels on some vegetative growth traits of date palm tissue cultured derived plants.The concentrations of polyethylene (zero, 20 and 40 mg.L-1) and salicylic acid (zero, 50 and 100mg.L-1). The experiment carried out using randomized complete design and factorial in three replications. The results showed that increasing the concentration of polyethylene led to increased paperwork content of chlorophyll B and the total and received an increase the nitrogen percentage in the papers. The impact of the concentration of acid, salicylic has said the results of a significant increase in chlorophyll, A, B and macro as well as an increase in the percentage of dry matter and an increase in the percentage of nitrogen in securities The impact of interaction between the polyethylene acid, salicylic, the results showed that there was a significant increase in most the traits in study.